Does the university knowledge spillover promote common prosperity? Empirical evidence from China - Di Mao; Jiakeng Chen (Humanities & Social Sciences Communications)
Abstract The 2030 Agenda for Sustainable Development emphasizes the need to foster inclusive economic growth and reduce inequalities across regions. Common prosperity is a national goal in China that emphasizes social equality and shared economic growth, which aligns closely with Sustainable Development Goals. While university knowledge spillover emerged as a critical approach to achieving these objectives, the pathways through which such spillover contributes to common prosperity remain underexplored. The aim of this study is thus to investigate the impact of university knowledge spillover on common prosperity through entrepreneurship. Based on a panel dataset of 30 provinces from 2012 to 2021, we employ the mediation effect model and reveal that university knowledge spillover significantly contributes to common prosperity, with entrepreneurship serving as an intermediary mechanism. Meanwhile, our results show that heterogeneity exists between geographical regions in the impact of university knowledge spillover on common prosperity, and university knowledge spillover has a greater influence on the “prosperity” dimension of common prosperity than on the “commonality” dimension. Our study extends the existing literature on the Knowledge Spillover Theory of Entrepreneurship to the field of inclusive growth, bridging the gap between university knowledge spillover and its socio-economic outcomes. Policymakers are advised to strengthen regional absorptive capacity and enhance the entrepreneurial environment, particularly in underdeveloped regions, to maximize the potential of university knowledge spillovers in fostering common prosperity and advancing sustainable development.